CRISIS OF THE DIGNITY OF THE TEACHING STATE BASED ON EMPIRICALRESEARCH - Pawelec, Lidia; Kochanowski, Jan (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The profession of teacher has been a special profession for centuries because of its momentous mission in the area of education and upbringing of next generations of society. This brought far wider expectations ahead of it than before other professions. In the current reality, there is a widespread belief in the lack of authority and the crisis of the dignity of the teaching state. Is this situation the result of the omnipresent "fall" of values, or do the teachers themselves contribute to the extent to which they are perceived by society and students? I try to find answers to these questions in the text of the article. The crisis in the dignity of the teaching state described above is primarily associated with a change in the perception of their profession by the teachers themselves. This thesis is supported by research carried out among teachers, pupils and parents in the Świętokrzyskie Voivodship. Their goal was to get to know the opinions of these groups about the moral and ethical condition of the modern teacher. In order to obtain this information, a diagnostic survey, an observation and an interview were used.